Hiring the best and the brightest : a roadmap to MBA recruiting - Taguchi, Sherrie Gong, 1961- (AMACOM, 2002)
"Hiring the Best and the Brightest reveals how successful companies like Goldman Sachs, McKinsey, Bertelsmann, Yahoo!, General Mills, and select startups find and develop their own MBA talent. Incorporating proven ideas from more than 25 expert recruiters, the book takes you step-by-step through the entire recruiting process, from defining your organization's hiring needs, to attracting and interviewing candidates, to making the kinds of offers that can't be refused."--Jacket